2002
DOI: 10.1067/mva.2002.123324
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter experience with the Talent endovascular graft for the treatment of abdominal aortic aneurysms

Abstract: These midterm findings show a high degree of technical and procedural success achieved in a patient population with extensive comorbid medical illnesses with low perioperative morbidity and mortality rates. Further follow-up study will be necessary to determine the effectiveness of the Talent endograft for the long-term treatment of AAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(70 citation statements)
references
References 24 publications
3
64
2
1
Order By: Relevance
“…Treatment using EVAR has resulted in low rates of aneurysm expansion of 8.7% after 6 months of followup 15 and demonstrable sac shrinkage of 52% Ϯ 9.7% at 12 months. 23 Freedom from endoleak has been reported to be All-cause mortality 2 (1.5) Myocardial infarction 0 (0) Renal failure 0 (0) Respiratory failure 1 (0.7) Paraplegia 0 (0) Stroke 0 (0) Bowel ischemia 0 (0) Procedural blood loss Ն1000 mL 4 (2.9) Total 6 (4.4) a Major adverse events related to the delivery system, defined as for the enhanced Low Profile System group, by the presence of any of the listed events, observed Յ30 days after the procedure.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Treatment using EVAR has resulted in low rates of aneurysm expansion of 8.7% after 6 months of followup 15 and demonstrable sac shrinkage of 52% Ϯ 9.7% at 12 months. 23 Freedom from endoleak has been reported to be All-cause mortality 2 (1.5) Myocardial infarction 0 (0) Renal failure 0 (0) Respiratory failure 1 (0.7) Paraplegia 0 (0) Stroke 0 (0) Bowel ischemia 0 (0) Procedural blood loss Ն1000 mL 4 (2.9) Total 6 (4.4) a Major adverse events related to the delivery system, defined as for the enhanced Low Profile System group, by the presence of any of the listed events, observed Յ30 days after the procedure.…”
Section: Discussionmentioning
confidence: 97%
“…13,14 Previous reports evaluating the safety of the Talent stent graft demonstrate satisfactory results with low complication rates. [15][16][17] The initial reports of the pivotal trial indicated a deployment success rate of 98.7% and device or procedure related complications of only 3.7%. 9,18 Survival rates of 92.7% to 95.4% at 1 year and 50% to 80.3% at 5 years have been reported.…”
Section: Discussionmentioning
confidence: 97%
“…A recent report has been prepared summarizing the results of an FDA-sponsored investigational device exemption trial for high-risk patients [19]. In the US trial, all patients either had significant comorbid medical conditions or had a hostile abdomen.…”
Section: Enrollment In Phase II Trial Completed the Medtronic Talent mentioning
confidence: 99%
“…This was significantly higher (14.1%) in the open exposure group. 6 Many studies support a reduction in groin complications, including wound infection, seroma, hematoma, lymph leak, and pseudoaneurysm, 34,44 when the percutaneous approach is used for endovascular repair of aneurysms. One such study quoted a >30% incidence of groin complications with EVAR compared with a <10% complication rate with PEVAR.…”
Section: Closure Devices For Endovascular Interventionsmentioning
confidence: 99%